Cavities Causes, diagnostics and Methods of Treatment and Prevention of Moderate Cavities - Aleksandrovna, Vinokurova Karina; Alekseevna, 2Zolikova Ekaterina (International Journal of Psychosocial Rehabilitation, 2020)
Cavities is the most common dental pathology, accompanied by necrosis of their tissues. Most researchers claim that an adult person at least once in a life goes to a dentist about cavities. However, most often the pathology occurs in people and elderly people. Most often, the enamel is affected, but the carious lesion can spread deeper up to the dentin or pulp. Among the clinical and morphological forms of cavities, the most common are moderate and deep cavities. The moderate one is a borderline state between superficial and deep cavities.Although moderate cavity affects children and adolescents more often than adults, this defect is often observed on baby teeth. According to the clinical course, cavity is divided into acute and chronic; by localization it is divided into cervical, fissure and proximal.The article tells about the causes of such a defect, methods of diagnosis and treatment.The work is based on data collected in Novosibirsk during the examination and after the patient's treatment by a dentist. The patient was diagnosed with cavity of the 2nd molar of the lower jaw and developed a treatment scheme for this pathology.